From design to action: Evidence of implementation and scaling up of agroclimatic services in Guatemala - Zapata Caldas, Emmanuel; Bonilla-Barrillas, Melissa; Martinez, Karen; Lopez, Sebastian; Londoño, Juan Manuel; Chavarro, Monica; Navarro, Carlos (2025)
English: This document synthesizes the evidence of the implementation and scaling up of community-based agroclimatic bulletins in Guatemala, developed between 2022 and 2025 using human-centered design and gender and social inclusion approaches. After three years of learning and collaborative work with key actors in the public and private sectors, the report documents how the bulletins evolved toward territorial implementation and actual use by small-scale farmers. During 2025, the Implementation phase focused on three areas: i) the co-design and initial testing of a bulletin generator; a free-access web platform that simplifies the creation and export of the bulletin through forms and real-time preview; ii) the preparation and implementation of a monitoring and evaluation exercise between August and September to measure the bulletin's reach, comprehension, use in agricultural decisions, and community circulation; and (iii) the scaling up of the co-design process for community bulletins in Huehuetenango, Quiché, and Petén through funding received from the Scaling Challenge. The results of dissemination with extension agents suggested significant circulation in local networks (at least 35 WhatsApp groups and 3 Facebook pages), while monitoring with farmers showed high acceptance of the “capsule” visual format: in Chimaltenango (n=26), over 90% perceived clarity and usefulness, 70% shared the information, and 90% recommended it; even so, opportunities for improvement in readability and the need for mediation were identified in some cases. In Santa Rosa (n=13), although independent comprehension was limited, most reported using the bulletin for agricultural decisions and sharing it, demonstrating moderate appropriation and potential for improvement. The report concludes with cross-cutting lessons on autonomous understanding, early multi-channel dissemination agreements, organization of information according to frequency of use, and mapping of the agroclimatic information flow "data journey" to reduce delays and strengthen the sustainability of community bulletins.